2018
DOI: 10.1097/md.0000000000011835
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of point mutations in the 23S rRNA gene in Helicobacter pylori eradication

Abstract: Clarithromycin-based triple therapy is prescribed worldwide for Helicobacter pylori eradication. However, increases in the clarithromycin resistance of H pylori are thought to be responsible for eradication failure. Here, we studied whether point mutations in domain V of the 23S rRNA gene can affect H pylori eradication failure in a prospective, open-label, observational study. Of the 755 enrolled patients, 299 patients (39.6%) had positive Campylobacter-like organism (CLO) tests. DNA sequencing analysis of H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 29 publications
7
26
0
Order By: Relevance
“…In addition, despite the weakness of the DPO‐based multiplex PCR method detecting only two subtypes of point mutations, the presence of point mutations was identified as a unique significant predictive factor for the success of eradication therapy in both the concomitant therapy and tailored therapy groups. The results of previous studies that suggest that the A2143G point mutation is the most important subtype associated with the in vivo eradication rate can be a reasonable explanation for our result …”
Section: Discussionsupporting
confidence: 85%
“…In addition, despite the weakness of the DPO‐based multiplex PCR method detecting only two subtypes of point mutations, the presence of point mutations was identified as a unique significant predictive factor for the success of eradication therapy in both the concomitant therapy and tailored therapy groups. The results of previous studies that suggest that the A2143G point mutation is the most important subtype associated with the in vivo eradication rate can be a reasonable explanation for our result …”
Section: Discussionsupporting
confidence: 85%
“…Among the point mutations identified, 21.3% were clinically significant; among those, A2143G was the most common point mutation (19.5%). The same result was observed in previous studies 19,21,22 .…”
Section: Discussionsupporting
confidence: 92%
“…however, its clinical significance has not been determined 15,22,23 In the present study, there was a significantly lower eradication rate in the 7-day PAM treatment group of clarithromycin resistance compared with that in the 7-day PAC treatment group of negative clarithromycin resistance [ITT; 55.4% (51/92) vs. 74.3% (252/339), P = 0.001, PP; 66.2% (51/77) vs. (131/138), P = 0.004]. In this study, a 7-day PAM regimen was used to treat clarithromycin-resistant H. pylori similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggested that the 2143G point mutation in the 23S rRNA was a risk factor for eradication failure and the presence of 2143G was significantly associated with female sex. 37 Our study also shows that the primary and secondary resistance rates of H. pylori to amoxicillin are 5.5% and 11.7%, whereas these rates to tetracycline are 12.9% and 30.0%, respectively. A prospective serial study conducted in Beijing of China found that the primary resistance rates of H. pylori were 6.7% and 4.9% to amoxicillin and tetracycline.…”
Section: Discussionsupporting
confidence: 69%